Causal effects of lipid-lowering drugs on skin diseases: a two-sample Mendelian randomization study - Liu, Yong; Liu, Hui; Bian, Queqiao (Frontiers in Medicine, 2024)
Background Although previous studies have indicated an association between low-density lipoprotein (LDL) and skin diseases, their causal effects remain inconclusive. This study aimed to assess the causal relationship between genetically proxied lipid-lowering drugs and skin cancers and psoriasis. Methods Two-sample Mendelian randomization (MR) analysis was performed using single-nucleotide polymorphisms (SNPs) from genome-wide association studies (GWAS). The inverse-variance weighted (IVW) method was used to determine causal relationships. The “leave-one-out” sensitivity test, Cochran’s Q-statistic and MR-Egger intercept were used to assess heterogeneity and horizontal pleiotropy. Results We identified 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) and proprotein convertase subtilisin-kexin type 9 (PCSK9) as genetically proxied lipid-lowering drugs. Genetically proxied inhibition of HMGCR (stains) was causally associated with reduced risk of nonmelanoma skin cancer (OR 0.982, 95% CI 0.967–0.997, p = 0.016 by weighted median; OR 0.977, 95% CI 0.966–0.989, p < 0.001 by IVW) and psoriasis (OR 0.585, 95% CI 0.378–0.905, p = 0.016 by IVW), while PCSK9 inhibition (alirocumab) was causally associated with reduced risk of psoriasis (OR 0.560, 95% CI 0.413–0.761 by weighted median; OR 0.564, 95% CI 0.447–0.712 by IVW; p < 0.001) in the ieu-b-5089 dataset. Similar results were observed in the ieu-b-110 dataset for HMGCR and PCSK9. Sensitivity analysis revealed no evidence of heterogeneity or horizontal pleiotropy. Conclusion This study revealed the existing HMGCR inhibitors (stains) might be protective for reducing nonmelanoma skin cancer risk, and HMGCR inhibitors (stains) and PCSK9 inhibitor (alirocumab) might be promising for reducing psoriasis risk in the European population.